PENGARUH ATRIBUT SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN TRANSJAKARTA - Tommy Setiawan Ruslim (Jurnal Manajemen., 2012)
Transportation is a very important factor in everyday life, good for travel to work, or recreation roads, making transportation is needed by every human being. Both private vehicles, as well as public transport, very dense visible everywhere, especially in the capital city of Jakarta. We can see the traffic is so dense creeping everywhere, both two-wheel or four-wheel drive, very fulfilling of the city. Busway with a number of amenities such as pathways, especially the passengers can make it more comfortable to avoid congestion, and also a place that was covered from the rain stops, and buses are used also has air conditioning, unlike other buses such as the mini metro, etc.. Rates are flat, like a taxi ride is not dependent on long distance destinations nearby, can make the busway as the right choice for those who want to go to the destination, but the Transjakarta should also pay attention to what the service provided to customers are satisfied or not. This study was conducted to determine whether there is a significant influence of service quality to customer satisfaction on Transjakarta. By taking a sample of 60 respondents, after processing the data, the results obtained have a significant influence of service quality attributes to customer satisfaction on Transjakarta.